PELATIHAN PERATURAN FUTSAL DAN MENJADI PELATIH TIM FUTSAL - Hari Pamungkas; Muhammad Nidomudin; Havid Yusuf; Miftah Rakhmadian; Khusnul Hotimah (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2022)
The purpose of this community service is to provide thorough knowledge of the FIFA standard futsal rules, and also provide basic knowledge on how to become a futsal team coach in the form of training activities. The methods or stages carried out in training activities go through 4 stages, namely the stages of observation, planning, implementation, and evaluation. The result of community service is that the implementation team has completed activities in the form of training on futsal rules and how to be a good coach for a futsal team. This training activity received very good feedback from participants and from invited practitioners, it is hoped that this activity can be carried out periodically to provide insight and knowledge to students and alumni of IKIP Budi Utomo Malang for each generation.